Individualization of the ANCA associated vasculitis treatment - Zbigniew Zdrojewski (Rheumatology, 2014)
Vasculitides associated with the presence of anti-neutrophil cytoplasmic antibodies (AAV) are the group of systemic diseases characterized by necrotizing inflammation of small and medium size vessels, without immunologic deposits and presence of circulating specific antibodies. Recent genetics and cohorts study should improve comprehension of pathogenesis of AAV, stratification patients in homogenous group and should progress therapeutic implication. Immunosuppressive therapy of AAV includes two major periods: first induction of remission, second maintenance therapy. It should be dedicated individually not only depending on the stage and severity of the disease but also on genetic and some prognostic factors. Previous randomized trials and clinical observations show some possible limitations of treatment with cyclophosphamide and steroids. Rituximab seems to be a good alternative in those patients in induction therapy as well as in maintenance therapy.